Detection of Biological Agents for the Prevention of Bioterrorism - Banoub, Joseph (NATO Science for Peace and Security Series A: Chemistry and Biology, 2011)
The threat of biological and chemical terrorism has driven the demand for timely techniques that can quickly detect the agent or agents used in an attack. The detection and/or prevention of these potential security threats provide significant scientific and technical challenges due to the combination of possible agents and modes of delivery available. This book will present a thorough look at the importance and technological challenges of mass spectrometry (MS) for the detection & identification of biological and chemical threats. This new contribution's general aims are to draw the attention of recognized practitioners, experts and graduate students trying to grasp the latest MS developments in the cutting-edge fields of MS-biodefense technologies for the rapid/early/specific sensitive threat detection of pathogens, viruses, explosives, mycotoxins, chemical agents, and biological markers of xenobiotic chemicals.